Power Quality Improvement of a Distribution Network for Sustainable Power Supply - Peter, Ohanu Chibuike; Benedict, Ohanu Ifeanyi; Chinweoke, Ogbuefi Uche; Kenneth C, Odo (International Journal of Integrated Engineering, 2022)
This paper presents a heuristic technique for improving power quality of a distribution network for sustainable electric power supply using shunt capacitor placement. The issue of power loss has been a major threat to a distribution network. A distribution network is expected to operate at certain voltage level to meet consumer’s energy demand. Power flow studies has been conducted using the Newton Raphson’s technique at the 30 bus, 11 kV Onuiyi-Nsukka distribution network. It was found that the voltage profile at buses 19 and 26 were critically violated with voltage amplitudes of 0.72 pu and 0.79 pu respectively. The feeder power quality was improved using a heuristic technique and the installation of a 1200KVAr shunt capacitor to keep bus voltage amplitudes within the legal limit of (0.95-1.05) pu. The voltage profile, active and reactive power losses on the network were determined. Active power loss and reactive power loss was reduced from 0.27MW to 0.12MW and 0.76Mvar to 0.14Mvar, respectively. Therefore, the voltage profile is enhanced and the power loss significantly reduced.